Responses of wintering Brent Geese to human disturbance - Owens, N W (Wildfowl, 1976)
An assessment is given of the effects of human disturbance on the distribution and behaviour of Dark-bellied Brent Geese Branta bernicla bernicla wintering in Essex. Disturbed areas and places with poor visibility were avoided in early winter, but were used later when other areas became depleted of food. Geese became partially habituated to the proximity of people and to some loud noises, but not to small low-flying aircraft. Disturbance could be greatly reduced by restricting access to the sea wall in certain areas around high tide, and by controlling low-flying aircraft.